Acute Pancreatitis Secondary to Dengue Fever: An Uncommon Presentation of a Common Endemic Illness - Miguel A. Flor; Jéssica V. Andrade; Jorge A. Bucaram (Case Reports in Infectious Diseases)
Dengue viral infection is considered endemic in Ecuador. It is more frequent during winter, caused by an RNA virus in the Flavivirus group. Its presentation can range from an asymptomatic state to hemorrhagic fever with shock signs. Acute pancreatitis could be a rare form of acute abdomen presentation associated with dengue virus infection. This case illustrates a 26-year-old man who presents to the hospital with cramp-like pain in the epigastrium and radiation to the right upper quadrant, accompanied by nausea and vomiting. He also endorsed additional symptoms such as throbbing-like headache, myoarthralgias, and fever of 40.4°C (104.72°F). Laboratory tests revealed elevated hematocrit, thrombocytopenia, elevated pancreatic enzymes, transaminitis, elevated alkaline phosphatase (ALP), and gamma-glutamyl transferase (GGT). Ultrasonography of the abdomen revealed hepatic steatosis, free fluid in the abdominal cavity, and small bilateral pleural effusions. Additional testing revealed IgM and IgG antibodies positivity to dengue virus. The patient was treated conservatively with intravenous (IV) fluid hydration and bowel rest. Acute pancreatitis should be considered when a patient presents with a suspected acute abdomen in the emergency department, and a detailed medical history is necessary to make a correct approach to the differential diagnosis.